Wind Speed Estimates for Garage Door Failures in Tornadoes - Jaffe, Aaron L.; Riveros, Guillermo A.; Kopp, Gregory A. (Frontiers in Built Environment, 2019)
Severe wind events, such as tornadoes, pose a significant threat to lives and infrastructure in many locations around the world. Residential buildings are the structures most affected by these events, since they are widespread and often not designed to withstand severe loading. For the wood-frame, low-rise houses typical of North America, once the envelope of the building has been breached, such as through the failure of a garage door, the loss of the entire roof structure becomes much more likely. One of the issues with garage doors is their flexibility; as they begin to deflect under wind load, relatively large openings allow air flow into the internal volume. As a result of these positive pressures on the garage door, positive pressures are transferred into the internal volume, subsequently reducing the net wind load on the door. The objectives of this study are to determine failure net pressures of garage doors through experimental testing, and to combine those results with internal pressure models including the effects of garage door flexibility in order to estimate the failure wind speeds of garage doors. Six garage doors of various types are tested, and the failure wind speeds acquired through the internal pressure model are compared to the Enhanced Fujita Scale. Experimental testing found the failure net pressures of the garage doors to be between 0.42 kPa and 1.75 kPa. With the internal pressure model showing that the net load on the garage doors is typically reduced to 34-46% of the external pressure, the resulting range of expected failure wind speeds obtained was 130-265 km/h. This range is found to encompass and exceed the expected failure wind speeds in the EF-Scale of 130-185 km/h, which would only be applicable for the weaker range of garage doors.